PENGARUH JENIS PELARUT PADA EKSTRAKSI KURKUMINOID DARI RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb) - Nurvita, Dyah Lasna (Chem Info Journal, 2013)
This study concerned in the effect of solvents on the extraction of curcuminoids from temulawak rhizome (Curcuma xanthorrhiza Roxb). Curcuminoids is one of the bioactive chemical constituents in rhizome of temulawak, known to have many benefits in the field of health and food. Bioactive ingredients may be extracted using ethanol, acetone, and ethyl acetate as solvent. Research that tries to investigate different solvents to obtain appropriate solvent in extracting has yet to be reported. This research was done by extraction using ethanol, acetone, and ethyl acetate, and defatization using n-hexane. The curcuminoids content was determined by UV-visible spectrophotometer at maximum wavelength of 427 nm. The results showed that acetone is the most appropriate solvent for the extraction of curcuminoids. It demonstrated the highest levels of total curcuminoids extracted with or without defatization